Trajectory of bodyweight and skeletal muscle mass in patients treated with nintedanib for idiopathic pulmonary fibrosis - Hiromi Tomioka; Takashi Fujikawa (Clinical Nutrition Open Science, 2024)
Summary: Background and Aims: Nintedanib is currently a therapeutic option for idiopathic pulmonary fibrosis (IPF). Weight loss is a common complication of IPF and a side effect of nintedanib, inducing loss of skeletal muscle mass and musculoskeletal dysfunction. Thus far, few clinical studies have investigated the relationship between skeletal muscle mass and bodyweight in patients with IPF receiving nintedanib. Methods: In this analysis, we evaluated pooled data obtained from a retrospective investigation of treatment with nintedanib for >6 months in patients with IPF. We assessed changes in bodyweight and skeletal muscle mass by determining the pectoralis major and minor muscle cross-sectional areas (PMcsa) by chest computed tomography before and after nintedanib therapy. Results: In the cross-sectional study (n=55), PMcsa at baseline was 13.0±3.0 cm2 and significantly correlated with age (r=−0.31, P=0.023), bodyweight (r=0.63, P<0.0001), and 6-min-walk distance (r=0.31, P=0.037). In the longitudinal study (n=33), significant PMcsa loss subsequent to the administration of nintedanib was observed (−1.1±1.4 cm2, 95% confidence interval: -1.6, -0.6, P=0.0001), and this effect was significantly related to weight loss (r=0.44, P=0.010). PMcsa loss was not significant during 6 months prior to nintedanib administration (−0.2±2.0 cm2, 95% confidence interval: -0.9, 0.5, P=0.60), and the observed changes were not significantly related to changes in bodyweight (r=-0.0347, P=0.848). Conclusions: Following treatment with nintedanib, significant skeletal muscle mass loss was recorded, and this effect was significantly associated with bodyweight loss. Monitoring of bodyweight is important during nintedanib therapy.